Fresh Gametes Might Get Better Clinical Results than Cryopreserved Sperm or Oocytes for Nonobstructive Azoospermia Patients Underwent micro-TESE - Yapeng Wang; Defeng Liu; Xiulian Ren; Shengli Lin; Ming Li; Hui Jiang; Ping Liu (IMR Press, 2022)
Background: micro-testicular sperm extraction (TESE) has been the first choice for Nonobstructive azoospermia (NOA) patients for its higher sperm retrieval rate under microscope, meanwhile, sperm or oocyte cryopreservation are widely applied in in-vitro fertilization (IVF) treatment. But few researches have systematically explored the effect of oocyte and sperm cryopreservation in one study. Methods: we retrospectively collected and analyzed the data of fertilization and pregnancy of patients who underwent micro-TESE using fresh or vitrified-warmed gametes in our center to assess the effect of gametes cryopreservation. Results: we compared the clinical results using fresh or vitrified-warmed gametes in NOA patients after micro-TESE, respectively. We found that the the rates of fertilization and good-quality embryo using fresh gametes were 52.37 ± 24.25% and 64.00 ± 36.18%, while these using vitrified sperm or oocyte were 46.00 ± 22.70% and 68.00 ± 34.6%, 45.51 ± 25.19% and 38.57 ± 31.08%, respectively; the rates of clinical pregancy and implantation using fresh gametes were 50.0% and 32.5%, while these using vitrified sperm or oocytes were 39.5% and 32.9%, 37.5% and 24.1%, respectively. The rates of good-quality embyo and clinical pregancy of the fresh gamete were above these of the vitrified, but there was no statistic difference. The live birth rate using fresh gamete was higher than that using the vitrified (47.1% verse 32.6%, 31.3%). Conclusions: The live birth rate using fresh gamete was higher than that using vitrified gametes. Fresh gametes showed better clinical outcomes than vitrified gametes in micro-TESE-ICSI treatment for NOA patients.